Stephen King : King of Thrillers and Horror - Wilson, Suzan (Berkeley Heights, NJ : Enslow Publishers, 2000)
Fiction
Includes bibliographical references (p. 124-125) and index.
"Books by Stephen King": (p. 112-114).
Keywords: King, Stephen; American authors -- Biography